Fundamentals and applications of nanoparticles for ultrasound‐based imaging and therapy. Issue 3 (24th July 2020) - Li, Lujing; Guan, Yupeng; Xiong, Haiyun; Deng, Tian; Ji, Qiao; Xu, Zuofeng; Kang, Yang; Pang, Jun
Abstract: Ultrasonography (US) is frequently applied in clinical imaging because of its inherent merits compared with those of other imaging methods. Nanoparticle (NP)‐based imaging and therapeutic modalities have been widely used because of their unique functionalities and high performance. The report is mainly about the classifications and applications of NPs for US‐based theranostic biomedicine. The US‐based applications include single‐modality US imaging, multimodality US imaging, high‐intensity focused US, US‐triggered drug release, US‐enhanced gene transfection, and US‐irradiated sonodynamic therapy. In addition, current challenges, including the biological effects and biosafety, are discussed in this interview. NPs have tremendous potential as a US‐based theranostic tool and have revealed a new direction in cancer therapy. Abstract : This review mainly focused on the unique functionalities and high performance of nanoparticles applied for ultrasound‐based imaging and therapy. Ultrasonic imaging can not only be used for guiding and monitoring the therapeutic process or efficiency of therapy, but also be developed as the physical tool for therapeutic applications.